1989
DOI: 10.1111/j.1365-2125.1989.tb05412.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma protein binding of frusemide in liver disease: effect of hypoalbuminaemia and hyperbilirubinaemia.

Abstract: The binding of frusemide was studied in the plasma of 20 healthy subjects and 45 patients with liver disease. The unbound percentage (mean +/‐ s.d.) of frusemide was 1.64 +/‐ 0.21 healthy subjects) and 2.24 +/‐ 0.79 (patients) (P less than 0.01). By grouping the patients on the basis of plasma albuminaemia and bilirubinaemia four clusters namely: 'normal concentrations of albumin and bilirubin' (A), 'hyperbilirubinaemia and normal albumin concentration' (B), 'hypoalbuminaemia and normal bilirubin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…However, in chronic disease states, such as chronic hepatic dysfunction and CKD, the DDI indices of drugs should be higher because of an increased proportion of unbound drugs. Furthermore, patients with chronic hepatic dysfunction or CKD frequently have hypoalbuminemia, which also results in an increase in protein-unbound drugs (Viani et al, 1989;Meijers et al, 2008). It has also been reported that, compared with control subjects, dialysis patients have significantly lower levels of albumin (Małgorzewicz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, in chronic disease states, such as chronic hepatic dysfunction and CKD, the DDI indices of drugs should be higher because of an increased proportion of unbound drugs. Furthermore, patients with chronic hepatic dysfunction or CKD frequently have hypoalbuminemia, which also results in an increase in protein-unbound drugs (Viani et al, 1989;Meijers et al, 2008). It has also been reported that, compared with control subjects, dialysis patients have significantly lower levels of albumin (Małgorzewicz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A sharp rise in bilirubin saturates the binding sites on serum protein, thus reducing the availability for phenytoin and potentiating free phenytoin concentration. This effect has been demonstrated with other protein-bound drugs in patients with a similarly deranged biochemical picture 5 6…”
Section: Discussionmentioning
confidence: 63%
“…Furosemide protein-binding alterations occurred in the presence of liver dysfunction but only when bilirubin concentrations exceeded 4 mg/dL and/or at albumin concentrations less than 3 g/dL. 20 This study did not measure furosemide blood concentrations. Further investigation of this topic is warranted.…”
Section: Review Of the Literaturementioning
confidence: 87%